2002
DOI: 10.1530/eje.0.1470417
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between malnutrition and ovarian hormones on the systemic IGF-I axis

Abstract: Objective: In malnutrition both the GH -IGF and reproductive axes are greatly affected. Because the actions of IGF and sex steroids are inter-dependent in many tissues, we have examined how ovariectomy modulates the response of the systemic IGF system to undernutrition. Design and methods: Peripubertal (30 days of age) female rats were either sham operated or ovariectomized. Five days later half of each group was submitted to a protein-caloric restriction diet. All rats were killed at 60 days of age. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
1
9
1
Order By: Relevance
“…Circulating IGFBP levels may be affected by nutritional and catabolic states. Calorierestriction has been shown to increase IGFBP-1 and IGFBP-2, whereas decrease IGFBP-3 levels [42]. However, our results suggested that local ventricular expression of IGFBP-3 may not be affected in the same manner as the circulating IGFBP-3.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Circulating IGFBP levels may be affected by nutritional and catabolic states. Calorierestriction has been shown to increase IGFBP-1 and IGFBP-2, whereas decrease IGFBP-3 levels [42]. However, our results suggested that local ventricular expression of IGFBP-3 may not be affected in the same manner as the circulating IGFBP-3.…”
Section: Discussioncontrasting
confidence: 55%
“…However, our results suggested that local ventricular expression of IGFBP-3 may not be affected in the same manner as the circulating IGFBP-3. Since undernutrition may cause a significant reduction in serum IGF-1 levels [42], the upregulation of ventricular IGF receptor may be a compensatory mechanism to ''make up'' for the heart growth at early stage of gestational nutrient deficiency. However, with persistent nutrient deficiency and over expressed IGF receptor, the effect of IGF cascade on heart development may switch from a compensatory beneficial effect to the detrimental hypertrophic one.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show similar trends for the relationship of malnutrition and brain IGF in other brain areas. For example, refeeding following food restriction leads to high levels of IGF-1 that persist into postnatal development and prolong the normal developmental time course (Chowen et al, 2002; Goya et al, 2002). A similar event may occur following sodium repletion at E12, potentially resulting in molecular/cellular alterations in the NTS that change the normal development of primary afferent terminal fields.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are many other related factors in serum, including calcium, 25-hydroxyvitamin D3, and thyroid hormone, which are combined and lost in urine with their associated binding proteins; all of the above exert effects on growth. Malnutrition or hypoproteinemia is another important cause of growth retardation in NS children (17), which is still poorly understood. "Catch-up growth", known as the phenomenon that the linear growth rate usually exceeds the normal range, was observed after a period of growth inhibition.…”
Section: Discussionmentioning
confidence: 99%